CRISPR deletion of a SINE-VNTR-Alu (SVA_67) retrotransposon demonstrates its ability to differentially modulate gene expression at the MAPT locus - Fröhlich, Alexander; Hughes, Lauren S.; Middlehurst, Ben; Pfaff, Abigail L.; Bubb, Vivien J.; Koks, Sulev; Quinn, John P. (Frontiers in Neurology, 2023)
Background SINE-VNTR-Alu (SVA) retrotransposons are hominid-specific elements which have been shown to play important roles in processes such as chromatin structure remodelling and regulation of gene expression demonstrating that these repetitive elements exert regulatory functions. We have previously shown that the presence or absence of a specific SVA element, termed SVA_67, was associated with differential expression of several genes at the MAPT locus, a locus associated with Parkinson’s Disease (PD) and frontotemporal dementia. However, we were not able to demonstrate that causation of differential gene expression was directed by the SVA due to lack of functional validation. Methods We performed CRISPR to delete SVA_67 in the HEK293 cell line. Quantification of target gene expression was performed using qPCR to assess the effects on expression in response to the deletion of SVA_67. Differences between CRISPR edit and control cell lines were analysed using two-tailed t-test with a minimum 95% confidence interval to determine statistical significance. Results In this study, we provide data highlighting the SVA-specific effect on differential gene expression. We demonstrate that the hemizygous deletion of the endogenous SVA_67 in CRISPR edited cell lines was associated with differential expression of several genes at the MAPT locus associated with neurodegenerative diseases including KANSL1, MAPT and LRRC37A. Discussion This data is consistent with our previous bioinformatic work of differential gene expression analysis using transcriptomic data from the Parkinson’s Progression Markers Initiative (PPMI) cohort. As SVAs have regulatory influences on gene expression, and insertion polymorphisms contribute to interpersonal differences in expression patterns, these results highlight the potential contribution of these elements to complex diseases with potentially many genetic components, such as PD.